The Influence of Interpersonal Conflict, Job Stress, and Work Life Balance on Employee Turnover Intention - Fathulla Ahmad, Dr. Ahmad (International Journal of Humanities and Education Development (IJHED), 2022)
Staff providing services to clients is a common feature of the private sector. To remain competitive, the private sector must maintain high-quality and consistent services. The aim of this study to analyze the influence of interpersonal conflict, job stress, and work life balance on employee turnover intention. Quantitative research was applied to measure the current study. A random sampling method was used to gather data. The researchers distribute 120 questionnaires. 112 questionnaires were received but only 104 questionnaires were valid. The findings revealed that the value B for Interpersonal conflict factor is .611 (.611>0.01) therefore first research hypothesis was supported. The value B for Job stress factor is .599 (.599<0.01) therefore second research hypothesis was supported. The value B for Work life balance factor is .643 (.643>0.01) therefore third research hypothesis was supported. Although the literature shows that turnover has a negative impact on many organizations, this study provides evidence that this relationship has an impact on the pesticide sector in this region.